A nominalização como estratégia de relativização - Camacho, Roberto Gomes [UNESP] (My University, 2010)
This work aims to present some results obtained from a typological research on relative clauses developed in a sample of Amazonian native languages. These results, which are specifically addressed to the distribution of the relativization strategies in the sample, intend to show, on one hand, that the use of nominalization consists in fact of an alternative strategy and, on the other hand, that some languages which take the nominalization as a primary strategy of relativization lack a specific class of adjectives.

O objetivo deste trabalho é apresentar alguns resultados obtidos de uma pesquisa tipológica sobre orações relativas com base numa amostra de línguas nativas da Amazônia. Esses resultados, que são especificamente voltados para a distribuição das estratégias de relativização, pretendem demonstrar, por um lado, que o uso da nominalização consiste, de fato, em uma estratégia alternativa e, por outro, que algumas línguas, que assumem a nominalização como uma estratégia primária estão privadas de uma classe específica de adjetivos.
The nominalization as a relativization strategy
Keywords: estratégias de relativização; nominalização; linguística tipológica; relativization strategies; nominalization; typological linguistics